Self-confidence in young athletes: A protective factor against perfectionism and anxiety in competitive grassroots sport - González-Hernández, J.; Barrera-Vázquez, D.; Gómez-López, M. (Perceptual and Motor Skills, 2024)
Perfectionism includes various dimensions focused on different planes of psychological functioning, with both positive and negative elements that influence adaptation to the pursuit of achievement and personal satisfaction with efforts and their attainment. We examined participants` levels of perfectionism and the relationship between perfectionism and anxiety in young athletes, and we described the mediating factor of self-confidence as a determinant of sport performance. We utilized a non-experimental, descriptive, and transversal research design. A total of 263 Spanish young athletes (M age = 15.79 years; SD = 1.07) who belonged to different sports clubs and engaged in different sports completed the Frost Multidimensional Perfectionism Scale (FMPS) and the Competitive Anxiety Inventory (CSAI-2R). Our results confirmed our belief that self-confidence was a protective factor for diminishing the negative relationships between perfectionism, anxiety, and sport performance. Regarding the predictive power of these variables, the construction of exaggerated achievement expectations (or personal standards) by combining functional and dysfunctional resources was reflected in cognitive anxiety (dysfunctional) and was mediated by self-confidence (functional). Application of these elements into training via well planned communication may allow coaches to enhance young athletes` resources for mental and behavioral adjustment toward their sporting goal. In addition, this training approach may underscore athletes` self-perceived competence and enhance their self-confidence.